The Maidan Massacre in Ukraine: The Mass Killing That Changed the World - Katchanovski, Ivan (Rethinking Political Violence Series, 2024)
Intro -- Preface -- Contents -- List of Figures -- List of Tables -- 1 Introduction: The Massacre That Changed Ukraine and the World -- 1.1 The Maidan Massacre and Its Impact -- 1.2 Data and Methodology -- 1.3 Theoretical Framework -- References -- 2 Conflicting Narratives of the Maidan Massacre in Ukraine -- 2.1 Conflicting Government Narratives of the Maidan Massacre -- 2.2 The Media Coverage of the Maidan Massacre -- 2.3 Misrepresentation of the Maidan Massacre by Wikipedia -- 2.4 Previous Academic Studies of the Maidan Massacre -- References -- 3 Video Reconstruction and Content Analysis of the Maidan Massacre on February 20, 2014 -- 3.1 The Reconstruction of the Snipers' Massacre of the Police and the Protesters on the Maidan in Ukraine -- 3.2 Shooting at Western, Polish, and Russian Journalists During the Maidan Massacre -- 3.3 Overthrow of the Yanukovych Government -- References -- 4 Testimonies of Several Hundred Witnesses and 14 Self-Admitted Maidan Snipers -- 4.1 Testimonies by Over 300 Witnesses Concerning Maidan Snipers -- 4.2 Confessions by 14 Self-Admitted Members of Maidan Sniper Groups -- References -- 5 Trial and Investigation Testimonies of Wounded Maidan Activists and Witnesses -- 5.1 Testimonies of Wounded Maidan Activists Concerning Snipers in Maidan-Controlled Locations -- 5.1.1 Hotel Ukraina Snipers -- 5.1.2 Zhovtnevyi Palace Snipers -- 5.1.3 Bank Arkada Snipers -- 5.1.4 Muzeinyi Lane, Music Conservatory, and Other Maidan-Controlled Locations Snipers -- 5.1.5 Staged Wounding of a Female Maidan Medic -- 5.1.6 Government Forces-Controlled Buildings and Areas Snipers -- 5.2 Testimonies by Prosecution Witnesses and Relatives of Killed Maidan Activists Concerning Snipers in Maidan-Controlled Locations -- 5.3 Testimonies of Defense Witnesses Concerning Maidan Snipers -- References.